EGFR-directed monoclonal antibodies in combination with chemotherapy for treatment of non-small-cell lung cancer: an updated review of clinical trials and new perspectives in biomarkers analysis. (January 2019) - Agustoni, Francesco; Suda, Kenichi; Yu, Hui; Ren, Shengxiang; Rivard, Christopher J.; Ellison, Kim; Caldwell, Charles; Rozeboom, Leslie; Brovsky, Kristine; Hirsch, Fred R.
Highlights: There is a strong rationale for targeting EGFR-pathway in NSCLC. Addition of EGFR-mAbs to CT provided clinical benefit to patients with NSCLC. EGFR FISH/IHC identify sub-populations which benefit from the addition of EGFR-mAb. Results of combining EGFR-mAbs and RT in many clinical trials remain controversial. Role of histology-driven, biomarker-enriched model based on EGFR-FISH and IHC. Abstract: Lung cancer still represents one of the most common and fatal neoplasm, accounting for nearly 30% of all cancer-related deaths. Targeted therapies based on molecular tumor features and programmed death-1 (PD-1)/programmed death ligand-1 (PDL-1) blockade immunotherapy have offered new therapeutic options for patients with advanced non-small-cell lung cancer (NSCLC). Activation of the epidermal growth factor receptor (EGFR)-pathway promotes tumor growth and progression, including angiogenesis, invasion, metastasis and inhibition of apoptosis, providing a strong rationale for targeting this pathway. EGFR expression is detected in up to 85% of NSCLC and has been demonstrated to be associated with poor prognosis. Two approaches for blocking EGFR signaling are available: prevention of ligand binding to the extracellular domain with monoclonal antibodies (mAbs) and inhibition of the intracellular tyrosine kinase activity with small molecules. There is a strong rationale to consider the tumor's level of EGFR expression as one of the most significant predictive biomarkers in this setting. In this paper we provide an update focusing on the current status of EGFR-directed mAbs use for the treatment of patients with advanced NSCLC, through a review of all clinical trials involving anti-EGFR mAbs in combination with chemotherapy (CT) for advanced disease and with chemo-radiotherapy for stage III disease. Here we also discuss the current status of predictive biomarkers for anti-EGFR mAbs when added to first-line CT in patients with advanced NSCLC. Finally, we focused on the relevance of EGFR fluorescence in situ hybridization (FISH)+ and immunohistochemistry (IHC)-Score ≥ 200 as predictive biomarkers for the selection of patients who would be most likely to derive a clinical benefit from treatment with CT in combination with anti-EGFR mAbs, with particular reference also to histology.